The Relationship of Noise Intensity and Hypertension in Communities Living Around Kendal Regency Railways - Istiqomah, Istiqomah; Setiani, Onny; Sulistiyani, Sulistiyani; Budiyono, Budiyono (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Railway traffic contributes significantly to noise pollution in urban areas, adversely affecting human health. This study focuses on the impact of train noise on hypertension among residents living near the Kendal Regency railroad tracks. With 105 participants residing within 0–30 meters from the tracks, aged 25–64, the study utilized purposive sampling to select 50 individuals. The average noise intensity measured was 73.1975 dBA, exceeding the permissible limit of 70 dBA. While the mean systolic and diastolic blood pressures indicated pre-hypertension, statistical analysis revealed a significant association between age and hypertension incidence (p = 0.042), with those over 40 facing a 4.5 times higher risk. However, no significant association was found between noise intensity and hypertension incidence (p = 0.292), systolic (p = 0.312), or diastolic blood pressure (p = 0.729). Additionally, factors such as distance from home, length of stay, rest, BMI, water consumption, and physical activity showed no significant association with hypertension incidence (p > 0.05). These findings suggest that while age is crucial in hypertension risk, noise intensity from railway traffic may not be a primary contributing factor. Further research is warranted to explore additional variables impacting hypertension in railway-adjacent communities.